Design and Implementation of a Canva-Based Animation Video to Enhance Understanding of Food Webs in Elementary Science - Yuliana; Hartono; Masagus Mhd. Tibrani (Jurnal Penelitian Pendidikan IPA, 2026)
This study aims to develop and implement instructional media in the form of Canva-based animated videos to improve students’ conceptual understanding of Food Webs in the Natural and Social Sciences (IPAS) subject for Grade V elementary school students. The development model employed is the Alessi & Trollip model, which consists of three main stages: planning, design, and development. The research subjects were Grade V students who participated in the learning process using the developed media. Research instruments included expert validation sheets, practicality questionnaires, and learning achievement tests in the form of pretests and posttests. The validation results indicate that the media achieved a very valid category, with an average score of 87.07%, covering language, content, and media aspects. Practicality testing conducted through individual trials and small group trials also showed very high results, with percentages of 97.33% and 74.40%, respectively. Effectiveness testing at the field trial stage revealed a significant improvement in students’ learning outcomes, with an average N-Gain score of 0.63, which falls into the moderate category. These findings demonstrate that Canva-based animated videos are effective in enhancing students’ conceptual understanding through the presentation of material that is visual, interactive, and contextual. Therefore, this instructional media is feasible to be implemented as an innovative alternative in IPAS learning at the elementary school level to strengthen concept mastery and increase students’ learning motivation